GAMBARAN DISTRIBUSI RABIES DI KABUPATEN SIKKA PROVINSI NUSA TENGGARA TIMUR 2004-2008 - Fridolina Mau; Yustinus Desato (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2011)
Rabies has long been known as one of the major public healht problems in Sikka district, East Nusa Tenggara Province, Indonesia. Flores is an isolated preveiously rabies- free. It started with the importation of three dogs from rabies endemic Sulawesi in September 1997. The rabies virus is present in the saliva of infected animals; all warm-blooded animals are susceptible to rabies, and some may serve as natural reservoirs of the virus. Rabies is still a problem for world health including Indonesia. Data of deathcase of rabies (lyssa) in Indonesia register 125 cases each year. Rabies in Indonesia is a serious health problem because almost fatal after clinical symptom of the disease with death rate of 100%. Since 2004 to December 2009 rabies spread to 24 provinces in East Nusa Tenggara Province. Number of cases due to bite of a mad dog was 16.000 cases. The aim of this study is to know distribution of rabies casse and the main control measures is immunizing dogs. Tipe of this study is cross sectional. The result of this study showed the improvement in the last five years (2004 until August 2008) of the occurences of dog bite in cases and human deaths highest in 128 cases (32,48%) in community health centers Waipare and population dog highest in Kewapante subdistrict 7213 (26,27%) although the coverage of immunization was very low that was 2523 (10,77%) out of 6210 population. In average the dog bite cases occurred in April.